Character Based Leadership In Higher Quality Improvement - Adil Makmur Santosa (International Journal of Education, Information Technology, and Others, 2022)
The leader has unique traits and personalities so that it is his behavior and style that distinguishes him from others. This lifestyle will definitely color his behavior and leadership type. Leadership is an aspirational force, a creative spirit, and a moral force, which is able to influence members to change attitudes, so that they are in line with the wishes and aspirations of the leader. We know that leaders should be role models for those they lead. Some types of leadership in general are autocratic, charismatic, laisser faire, democratic, to make quality improvements. But when it comes to giving orders or directions, it will cause difficulties, because in doing a good job, you have to wait for orders from the leadership, and if there is no order from the leadership, then the work is not done well, then continuous improvement in the quality of performance will be difficult to realize. A leader must be able to motivate his employees through a leadership style based on Indonesian Local Wisdom, namely a character-based leadership style. from College